2021
DOI: 10.1161/circresaha.120.318793
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Variants in SCARB1 Cause Severe Early-Onset Coronary Artery Disease

Abstract: Rationale: Coronary artery disease (CAD) is a pervasive and critical healthcare problem. Elevated high density lipoprotein-associated cholesterol (HDL-C) is associated with improved atherosclerotic cardiovascular disease (ASCVD) outcomes on a population level, but clinical trials aimed at HDL-C elevation have not succeeded in improving ASCVD event risk. Nevertheless, human variants in the HDL receptor, encoded by SCARB1, are associated with dyslipidemia, suggesting that HDL metabolism, not HDL-C, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Studies in mice showed that the absence of functional SR-B1 leads to increased plasma cholesterol concentrations, which is associated with enlarged HDL particles with increased unesterified cholesterol content and altered apolipoprotein composition [52][53][54][55][56]. Although inactivating mutations in the SCARB1 gene in humans are rare, similar increases in HDL cholesterol as well as early-onset coronary artery atherosclerotic disease were reported in human compound heterozygotes carrying two inactivating mutations in SCARB1 [57]. This is similar to findings in mice in which SR-B1 is knocked out in the context of other atherogenic mutations [54,58,59].…”
Section: Figure 1 Hdl and Sr-b1 Selective Lipid Exchangementioning
confidence: 92%
“…Studies in mice showed that the absence of functional SR-B1 leads to increased plasma cholesterol concentrations, which is associated with enlarged HDL particles with increased unesterified cholesterol content and altered apolipoprotein composition [52][53][54][55][56]. Although inactivating mutations in the SCARB1 gene in humans are rare, similar increases in HDL cholesterol as well as early-onset coronary artery atherosclerotic disease were reported in human compound heterozygotes carrying two inactivating mutations in SCARB1 [57]. This is similar to findings in mice in which SR-B1 is knocked out in the context of other atherogenic mutations [54,58,59].…”
Section: Figure 1 Hdl and Sr-b1 Selective Lipid Exchangementioning
confidence: 92%
“…Several polymorphisms of human SR-B1 have been identified in the human SCARB1 gene, including nine coding mutants: V32M, V111M, S112F, V135I, R174C, T175A, P297S, G319V, and P376L [ 21 ••, 22 ••, 76 , 77 , 92 •, 93 •, 94 •]. The locations of these mutants are mapped to our homology model (Fig.…”
Section: Human Relevance Of Sr-b1mentioning
confidence: 99%
“…V111 is predicted to be solvent exposed within an extracellular β-strand near the N-TMD and may impact SR-B1 membrane dynamics. G319V is within a solvent-exposed loop in our model and in vitro studies showed that G319V-SR-B1 exhibited a decreased capacity to mediate HDL-CE uptake compared to wild-type SR-B1, despite comparable levels of cell surface expression [ 22 ••]. Information from G319V-SR-B1 cellular assays, combined with a recent clinical observation of recurrent myocardial infarctions in a young adult with the G319V-SR-B1 mutation [ 22 ••], highlights the delicate balance of cholesterol homeostasis maintained by SR-B1.…”
Section: Human Relevance Of Sr-b1mentioning
confidence: 99%
See 2 more Smart Citations